The role of digitalization and inclusive climate in building a resilient workforce : An ability–motivation–opportunity approach - Zahoor, Nadia; Roumpi, Dorothea; Tarba, Shlomo; Arslan, Ahmad; Golgeci, Ismail (John Wiley & Sons Ltd, 2024)
Organizations need resilient employees to navigate and leverage constant change and maneuver in turbulent, disruptive contexts. As such, it is imperative to advance a nuanced understanding of drivers and enablers of employee resilience, especially in the current business context of pervasive digitalization and the growing practice of work-from-everywhere. Our research explores how digitalization in the organization is reflected in the employees' behavior of taking charge and resilience. By accounting for core self-evaluation, digital literacy, and inclusive climate boundary conditions, we offer a holistic picture of under what conditions digitalization enhances taking charge and employee resilience. To test our study model, we follow a survey research design and rely on 173 employees' data working in the United Arab Emirates (UAE). Our results show that digitalization is positively related to employee resilience. Further, our findings show that core self-evaluation, digital literacy, and inclusive climate moderate the impact of digitalization on employee resilience. Our results received further support in a two-wave online survey with 306 employees in the United States. The support we found for the hypothesized mediating relationship highlights the criticality of taking charge in relation to digitalization and employee resilience. Taking charge is critical in relatively turbulent environments as it helps employees deal with changes in processes, procedures, and structures.
Keywords: inclusive climate; core self-evaluation; taking charge; employee resilience; UAE; USA; digitalisation